The Impact of Extensive Reading of Novels on Students' English Vocabulary Acquisition - Elvriza, Meira Sintia; Ivan Achmad Nurcholis (Yayasan Pendidikan Genlita Indonesia, 2025)
This study examines the impact of extensive novel reading on vocabulary acquisition among students learning English as a foreign language (EFL). Extensive reading involves reading large amounts of material for pleasure and general comprehension, fostering a positive attitude toward reading and language learning. This method enables learners to engage with texts that interest them, promoting vocabulary growth. The study synthesizes findings from recent research, revealing that students engaging in extensive reading show significant vocabulary gains compared to those who do not. A semester-long program with EFL students allowed participants to select novels based on personal interest, with pre-and post-program assessments measuring vocabulary acquisition. Results showed a 30% average increase in vocabulary size, with students reporting improved confidence in using new words. Challenging texts led to greater vocabulary gains, while qualitative feedback highlighted increased motivation and engagement through enjoyable reading experiences. Students noted that encountering new words in context and discussing novels with peers enhanced comprehension and retention. These findings emphasize the importance of incorporating extensive reading into EFL curricula to enhance vocabulary acquisition and language proficiency. Future research should investigate long-term effects, retention, and the role of different genres in vocabulary development.